2019
DOI: 10.1029/2018rs006781
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Anomalous VHF Propagation Due to the Sporadic‐E Layer in the Air‐Navigation Band

Abstract: The sporadic-E (Es) layer is an ionospheric layer which appears occasionally near 100-km heights with extremely high electron density. The Es layer may reflect very high-frequency radio signals when the incident angle is shallow (Es layer anomalous propagation [EsAP]). It is known that radio signals with frequencies above 100 MHz sometimes reach distant locations, more than 600 km apart from the transmitters, due to EsAP. Since air-navigation radio channels are allocated on frequencies between 108 and 118 MHz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…We are most interested in ILS ID 17 on which very strong signal (>−95 dBm) is recorded continuously for more than 3 hr. A group of vertical traces at around 18 JST is supposed to be artificial noise (Sakai et al, 2019).…”
Section: Space Weathermentioning
confidence: 99%
“…We are most interested in ILS ID 17 on which very strong signal (>−95 dBm) is recorded continuously for more than 3 hr. A group of vertical traces at around 18 JST is supposed to be artificial noise (Sakai et al, 2019).…”
Section: Space Weathermentioning
confidence: 99%
“…E s layers have been studied extensively since the middle of the twentieth century because they cause anomalous propagation of radio waves utilized for communication and broadcast (e.g., Whitehead 1970). More recently, it became known that the E s layers have a potential impact on air-navigation applications using very high frequency waves (Sakai et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Es on analogue television and FM radio in such a frequency range have been well-known for a long time. Recently, Sakai et al (2019Sakai et al ( , 2020 demonstrated that propagation of VHF radio waves used for aeronautical navigation (so-called NAV signals at 108-118 MHz range) has also been affected by the appearance of Es. In particular, they statistically showed that Es anomalous propagation (EsAP) of NAV signals often occurs in Japan during summer months.…”
Section: Introductionmentioning
confidence: 99%